Supply Chain Management and Organisational Performance: Mediation Effect of Competitive Advantage - Charles Maina Wainaina; Eric Bett; Benard Njehia (International Journal of Supply Chain Management, 2021)
Supply chain management (SCM) practices have become valuable resources and capabilities in formulating strategies aimed at enhancing organizational performance (ORGPER). However, it is not clear how SCM Practices influence organizational performance in the agribusiness context. Therefore, this study sought to examine the mediation effects of competitive advantage in the relationship between SCMPs and ORGPER from the dairy supply chain perspective in Kenya. The study postulated four hypotheses that were tested using Partial least squares structural equation modelling (PLS-SEM) techniques to address the study objectives. A cross-sectional survey design was utilized to gather primary data from 109 dairy cooperatives in the thirteen major milk-producing counties in Kenya. The result revealed that SCM practices have a positive and significant influence on CA (?=0.730), and ORGPER (?=0.237). Additionally, CA has a positive, statistically significant influence on ORGPER (?=0.522). Further results show that competitive advantage mediates the relationship between SCMPs and organizational performance. Consequently, high employment of SCM practices will result in high levels of competitive advantage and enhance organizational performance. The results provide insights on the resource-based view theory as well as a conceptual framework for its validation. Similarly, the study informs managers and policymakers in knowing specific SCM practices responsible for enhancing competitive advantage and improving performance in the dairy industry. Keywords: Competitive advantage, Organizational performance, Supply chain management, and PLS-SEM